Avaliação dos hospitais universitários federais sob gestão compartilhada com a empresa brasileira de serviços hospitalares (EBSERH) - Ferlin, Meili Pereira (2020)
Federal University Hospitals (HUFs) perform fundamental activities in the Brazilian public health care network, mainly in medium and high complexity, in addition to being important training centers for health professionals when developing research and extension teaching actions. HUFs are linked to the structure of federal universities and are linked to the Ministries of Education and Health, playing an important role in the Unified Health System (SUS). In 2010, the Federal Government established the National Program for the Restructuring of Federal University Hospitals (REHUF), with the objective of creating structural, technological and institutional conditions to offer quality medical and hospital care to society, as well as providing adequate training for professionals in health area. In line with the objectives of the REHUF, in 2011, the Brazilian Hospital Services Company (EBSERH) was created to modernize the management and restructure the staff of HUFs. This context raised the guiding questions of this study: what is the influence of adherence in terms of physical, human and indicator resources? Was there an improvement in the performance of HUFs after joining EBSERH? This work aimed to carry out an evaluation of the performance of HUFs under shared management with EBSERH. As a methodological option, an applied and descriptive research was carried out ex post facto, that is, conducted based on the fact, which occurs naturally without the control of the researcher. A mixed, qualitative and quantitative approach was adopted, using the documentary bibliographic collection procedure, making use of a systematic survey of the characteristics of implantation of EBSERH in the country. Each HUF corresponded to a unit of analysis. Data were collected from the information systems DATASUS, CNES and SIHSUS in relation to the 40 HUFs that joined the shared management with EBSERH until 2018, among the 50 existing HUFs in the country. The monthly data of each HUF in the period of one hundred and twenty-one months, before and after the change of its management method, were consolidated on a single basis with the aid of the PostgreSQL software and, later, accessed from an electronic spreadsheet. The data analysis involved the study of the operational capacity represented by the time series of six indicators by HUF and by size, being two of process and four of result. As a result, it was concluded that joining the EBSERH did not translate into equity in the distribution of physical resources of the HUFs across the country's different geographical regions; as well as, that there was no improvement in the HUFs in relation to the performance indicators studied in the 40 HUFs; only 13 (32.50%) showed an improvement of 60% or more in the indicators, basically in TOH and IR; the other 27 hospitals remained below the index established by this research. Consequently, it is concluded that the implementation of the shared management policy was not able to produce the results idealized by REHUF, which still needs improvement.